Validation of the student athletes’ motivation towards sports and academics questionnaire to Korean student-athletes - Park, Sunghee (J Exerc Rehabil, 2015)
The current study had three aims: (1) to validate a Korean version of the Student Athletes’ Motivation toward Sports and Academics Questionnaire (SAMSAQ-Kr), (2) to examine South Korean university student-athletes’ motivation towards athletic and academic achievement, and (3) to identify the relationship between athletic identity and their athletic and academic achievement. A total of 126 South Korean university student-athletes (41.4% males and 58.6% females; mean age 20.5, SD = 2.74) completed the SAMSAQ-Kr. To investigate the validity evidence of the SAMSAQ-Kr a confirmatory factor analysis (CFA) and Rasch model were employed. To examine the relationship between Athletic Identity Measurement Scale (AIMS) and SAMSAQ for Spearman correlation coefficients were calculated. Findings indicated that the SAMSAQ-Kr showed a different model from other versions and revealed positive correlations between AIMS scores and athletic motivations. The current study highlighted that importance of considering socio-cultural context in developing questionnaire and contributed to help understand South Korean university student-athletes’ motivation towards athletic and academic achievement.